2016
DOI: 10.1002/aoc.3549
|View full text |Cite
|
Sign up to set email alerts
|

Terephthalic acid derived ligand‐stabilized palladium nanocomposite catalyst for Heck coupling reaction: without surface‐modified heterogeneous catalyst

Abstract: A new protocol is reported for the synthesis of a heterogeneous palladium nanocomposite stabilized with a terephthalic acid-derived ligand (N,N-bis(4-hydroxy-3-methoxybenzylidene)terephthalohydrazide). This is a highly insoluble ligand in common organic solvents, except dimethylformamide and dimethylsulfoxide. The resulting palladium nanocomposite acts as an efficient catalyst precursor for Mizoroki-Heck coupling reactions conducted under various reaction conditions. The spectral data suggest that the rate, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…It was also reported that o-phenylenediamine was used with alkyl, aryl, and heterocyclic aldehydes in the presence of palladium or some other copper compounds catalysis. From this reaction a good product and purity were obtained, Scheme 3 [31], [32] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was also reported that o-phenylenediamine was used with alkyl, aryl, and heterocyclic aldehydes in the presence of palladium or some other copper compounds catalysis. From this reaction a good product and purity were obtained, Scheme 3 [31], [32] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…On the other hand, the synthetic aspect of quinazolinone and its derivatives carried out by condensation reaction of isatoic anhydride, primary amine, or ammonium salts with aldehydes was widely employed. It was catalyzed by β-cyclodextrin-SO 3 H [12], nanoparticles [13,14], Saccharomyces cerevisiae (baker's yeast) [15], Montmorillonite K10 [16], cation-exchange resin [17], palladium [18], ionic liquid-water [19], and so on. A vast number of quinazolinone derivatives have been designed to provide effective drugs, especially some antifungal agents such as tryptanthrin [20,21] and 2acetylquinazolin-4(3H)-one [22,23].…”
Section: Introductionmentioning
confidence: 99%